KREATIVITAS GURU PAI DALAM PENGEMBANGAN BAHAN AJAR DI MADRASAH ALIYAH AL-AMIN BANDAR MASILAM - Nadia Dwi Utami; Nazwa Nabila Ningsih; Muhammad Wahyudi (Jurnal At-Tabayyun, 2022)
Creativity is the main factor that makes the learning process in the classroom effective and to achieve optimal educational learning goals. The purpose of this research is that teaching materials are conceptually a means of support in an effort to optimize the process of education and learning to achieve the goals expected by educational institutions. To achieve these objectives, this study uses a qualitative approach. Data collection techniques were carried out through observation/observations, interviews and documentation. Data analysis procedures are data reduction, data presentation, and verification. While the research subjects were the head of the madrasa, deputy head of the madrasa, and teachers of Islamic religious education. The results obtained describe that, (1) teachers in developing teaching materials in the PAI learning process at Madrasah Aliyah Al-Amin tend to have creativity, this form of creativity can be seen from the variety of teaching materials developed, either as a result of their own creations, provided by the library schools, purchased by stores selling them, or downloaded from various available websites such as available videos. Among the teaching materials used with various intensity of use and the quality of the teaching materials themselves, including: books, pictures, Al-Quran, Videos, Al-Quran and (2) constraints of Islamic religious education teachers in increasing the creativity of teaching materials, among others lack of understanding of elderly teachers.